SISTEM ENGINE ORDER TELEGRAPH DI ENGINE ROOM DENGAN KOMUNIKASI RS485 BERBASIS ARDUINO MEGA2560 (PPPM - POLITEKNIK PELAYARAN SURABAYA, 2022)
The EOT (Engine Order Telegraph) is the captain's safe and continuous embodiment of a human-machine interface as a basic part of a connected remote propulsion system. Remote control systems on modern ships usually have a control transfer system that allows control to be transferred between locations. Remote control is usually possible from two locations: the bridge and the Engine Control Room (ECR). Some ships do not have a remote control handle on the ECR. When in bridge control mode, the bridge hold directly controls the engine set point. When in Engine Control Room mode, the bridge handle sends a telegraph signal to the ECR and the ECR handle controls the control system set point. In local control, the remote control system is inactive and the bridge hold sends a telegraph signal to the local control position and the engine is operated by its manual control in the engine room. In this research, an EOT tool will be realized using the Arduino Mega2560 microcontroller and data communication using the RS485 serial from the bridge to the engine control room. The outputs of this research are prototypes of EOT tools, research reports, journal publications and HKI